Effect of polyethylene glycol on in vitro degradability of nitrogen and microbial protein synthesis from tannin-rich browse and herbaceous legumes (BRITISH JOURNAL OF NUTRITION, 2000)
Determination of microbial degradability of N is important in formulating a sound supplementation strategy for efficient utilisation of basal as well as supplementary diet components. In vitro degradability of N (IVDN) from tannin-containing browses (Acacia cyanophylla, Acacia albida, Acioa barteri and Quercus ilex) and two herbaceous legumes (Desmodium intortum andDesmodium uncinatum) was determined using the in vitro gas-production method coupled with NH3-N measurement in the presence and absence of a tannin-binding agent (polyethylene glycol (PEG), molecular mass 6000). Addition of PEG to tannin-containing feeds significantly (P < 0.05) increased in vitro gas and short-chain fatty acid (SCFA) production, and IVDN. The use of PEG as a tannin-binding agent increased IVDN from 28 to 59, 32 to 72, 19 to 40, 32 to 73, 40 to 80, and 26 to 77 % in A. cyanophylla, A. albida, A. barteri, D. intortum, D. uncinatum and Q. ilexrespectively. There was significant correlation between total phenolic compounds (total phenol, TP; total tannin, TT) in leguminous forages and percentage increase in IVDN on addition of PEG (P < 0.05; R-2 0.70 and 0.82 for TP and TT respectively). The difference in IVDN observed in the absence and presence of PEG indicates the amount of protein protected from degradation in the rumen by tannins. When measured after 24 h incubation, tannin-containing feeds incubated in absence of PEG resulted in higher microbial protein synthesis than in the presence of PEG. Addition of PEG significantly (P < 0.05) reduced the efficiency of microbial protein synthesis expressed as mu mol purine/mmol SCFA.